Interactions in the (Pre)metastatic Niche Support Metastasis Formation - Doglioni, Ginevra; Parik, Sweta; Fendt, Sarah-Maria (Frontiers in Oncology, 2019)
Metastasis formation is the leading cause of death in cancer patients. Thus, understanding and targeting this process is an unmet need. Crucial steps during the establishment of metastases include the (pre)metastatic niche formation. This process relies on the interaction of the primary tumour with the environment of distant organs (premetastatic niche) and the interaction of cancer cells with their environment when arriving in a distant organ (metastatic niche). Here, we summarize the current knowledge on the interactions in the tumour environment that result in (pre)metastatic niche formation in respect to tumour secreted factors, extracellular matrix, immune as well as stromal cells and the nutrients availability. We further highlight approaches to disrupt these interactions as therapeutic strategy against metastases.